2007
DOI: 10.1186/1471-2407-7-231
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose escalation study of vinorelbine and topotecan combination chemotherapy in patients with recurrent lung cancer

Abstract: Background: A platinum doublet is the current standard treatment for good performance status patients with advanced non-small cell lung cancer (NSCLC) and extensive stage small cell lung cancer (SCLC) with good performance status. However, platinum-based treatment may be associated with significant toxicities, therefore alternative platinum-free combinations should be investigated. Topotecan is a topoisomerase I inhibitor that exerts its cytotoxic effect through stabilization of the topoisomerase I-DNA complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This enzyme shows a diffuse pattern of distribution in the nucleoplasm with accumulation in the nucleolus [ 55 ]. The catalytic activity of TOPO I is specifically inhibited by camptothecin, an alkaloid of Camptotheca acuminata and similar drugs, such as topotecan (Hycantina®, GlaxoSmithKline) [ 56 , 57 ] and irinotecan (Camptosar, Pfizer) [ 58 , 59 ]. Camptothecin has powerful anti-tumor activity by inhibiting synthesis of nucleic acids and inducing breaks in DNA molecules ([ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme shows a diffuse pattern of distribution in the nucleoplasm with accumulation in the nucleolus [ 55 ]. The catalytic activity of TOPO I is specifically inhibited by camptothecin, an alkaloid of Camptotheca acuminata and similar drugs, such as topotecan (Hycantina®, GlaxoSmithKline) [ 56 , 57 ] and irinotecan (Camptosar, Pfizer) [ 58 , 59 ]. Camptothecin has powerful anti-tumor activity by inhibiting synthesis of nucleic acids and inducing breaks in DNA molecules ([ 60 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In our method, the dose increment in MCDIS was dependent on the initial dose. Some studies have used a constant dose increment but different magnitude of initial dose [ 24 , 25 ], and other studies have increased the dose with irregular increments [ 26 , 27 ]. In practice, the dose increments should be determined according to the pharmacological characteristics of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Beldner et al [ 19 ] conducted a phase I dose escalation study of vinorelbine and TPT combination therapy in patients with recurrent SCLC and NSCLC. The aim of this study was to evaluate the optimal dosage and the MTD of TPT and vinorelbine administered on an alternate dosing schedule.…”
Section: Phase I Clinical Trials Of Tpt As Combination Therapymentioning
confidence: 99%
“…In summary, phase I clinical trials done on TPT had shown good disease responses with minimal toxicity in combination with gemcitabine and vinorelbine at a dose range of 0.75 - 4 mg/m 2 /day given as infusion for 5 days every 3 weeks or as weekly bolus infusion for 3 weeks every 28 days [ 15 , 16 , 18 , 19 ]. TPT in combination with cisplatin is associated with high toxicity [ 14 ].…”
Section: Phase I Clinical Trials Of Tpt As Combination Therapymentioning
confidence: 99%